Histological and stable isotope analysis of archeological bones from St. Rombout's cemetery (Mechelen, Belgium): Intrasite, intraindividual, and intrabone variability. (3rd August 2022) - Kontopoulos, Ioannis; Van de Vijver, Katrien; Robberechts, Bart; von Tersch, Matthew; Turner‐Walker, Gordon; Penkman, Kirsty; Collins, Matthew J.
Abstract: This study compares histological preservation in archeological bones from different burial types to unravel the histotaphonomy‐to‐funerary practices relationship. Αn intraskeletal approach is also adopted to explore intraindividual (inner ear part of the petrous bone vs. upper/lower limb long bones) and intrabone (proximal vs. distal diaphysis) variability in bone collagen preservation, δ 13 C, and δ 15 N. The aim is to (a) target bones that likely retain higher amounts of collagen, (b) better understand the inner ear bone collagen isotopic signature and remodeling, and (c) assess intrabone isotopic and histological homogeneity. For the histological analysis, the data have been collected from 61 specimens (20 individuals) from the medieval/postmedieval cemetery of St. Rombout, Belgium. Thin sections have been studied using optical and scanning electron microscopy. For the collagen and isotopic data, 101 samples have been collected from 21 individuals. Distinct histological patterns are observed only in bones from single coffin burials; however, bone histology can display intraindividual and intrabone variability, which are important to account for interpretations. Collagen wt.%, δ 13 C, and δ 15 N show significant intraindividual differences but insignificant intrabone variability. This study also confirms the extraordinary nature of the petrous bone, as the inner ear bone collagen δ 13 C and δ 15 N values reflect the dietary input of the first approximately 2–3 years of life.